CLIC1 antibody conjugated nanoscale contrast agent as a sensitive and targeted molecular imaging probe for gallbladder cancer diagnosis. Issue 29 (2nd March 2016) - Lu, Wei; Wang, Ning; Chu, YanYan; Zhou, Linzhu; Li, Maolan; Huang, Tao; Weng, Hao; Zhang, Yijian; Jiang, Lin; Hu, Yunping; Tan, Qinggang; Liu, Yingbin
Abstract : CLIC1 antibody-conjugated nano-scale contrast agents exhibit a fast and sensitive detection of gallbladder tumors and may be used in the future as powerful targeted molecular imaging probes for gallbladder cancer diagnosis. Abstract : Limited by current clinical diagnosis techniques, gallbladder cancer remains a highly lethal disease and is associated with an extremely poor prognosis and treatment outcome. In an effort to overcome these severe obstacles, targeted nanoscale contrast agents have been developed and used in the past to increase the sensitivity and specificity of cancer detection. The development of targeted nanoscale contrast agents would offer an even more promising approach for gallbladder cancer diagnosis and subsequent treatment. In this study, a targeted nanoscale contrast agent was developed by conjugation of a CLIC1 antibody to carboxylated multi-walled carbon nanotubes (MWCNTs). Using a gallbladder cancer tumor xenograft model, it could be shown that intravenous injection of this tumor-targeted contrast agent to tumor-bearing mice exhibited a rapid photoacoustic signal with high intensity, leading to contrast enhancement of the entire tumor region. Mice injected with an untargeted contrast agent did not exhibit obvious tumor enhancement. We were able to show that CLIC1 antibody conjugated to nanoscale contrast agents proves to be highly beneficial for this fast and sensitive imaging technique for gallbladder tumors. Taken in concert, the results obtained indicate that the development of targeted nanoscale imaging probes offers a promising approach for the early detection and subsequent treatment of gallbladder cancer.